2022
DOI: 10.3390/molecules27249003
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic and Antioxidant Effect of Phytoecdysteroids and Polyphenols from Chenopodium quinoa on an In Vivo Restraint Stress Model

Abstract: The variety of stressful conditions in daily human activity requires nutritional support with safe, specialized food products containing functional food ingredients (FFIs) enriched with biologically active plant substances with proven adaptogenic properties. In this in vivo study, by evaluating a set of physiological parameters and biochemical markers, we investigated the effectiveness of the developed FFIs from Chenopodium quinoa grains in stress conditions induced by daily episodes of immobilization for 36 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Supplementation with quinoa and chia seed extracts may regulate metabolic indicators and showed hepatoprotective, anti-inflammatory, and antioxidant activities in rats [212]. Quinoa extracts showed anti-obesity, antioxidant, hypoglycemic, immunoregulatory, and collagenase-modulating effects in in vivo experiments with rats [208][209][210][211][212][213][214]. No serious adverse effects were reported within the experiments, which correlated with the safety profile of quinoa extracts and their safe nutrition in sports.…”
Section: Chia and Quinoa Seed Extractsmentioning
confidence: 61%
See 1 more Smart Citation
“…Supplementation with quinoa and chia seed extracts may regulate metabolic indicators and showed hepatoprotective, anti-inflammatory, and antioxidant activities in rats [212]. Quinoa extracts showed anti-obesity, antioxidant, hypoglycemic, immunoregulatory, and collagenase-modulating effects in in vivo experiments with rats [208][209][210][211][212][213][214]. No serious adverse effects were reported within the experiments, which correlated with the safety profile of quinoa extracts and their safe nutrition in sports.…”
Section: Chia and Quinoa Seed Extractsmentioning
confidence: 61%
“…al. revealed that quinoa effectively normalized oxidative stress markers and improved cognitive function [209]. Meneguetti et al reported that hydrolyzed quinoa decreased body weight, blood triacyl-glycerol level, and fat deposition [200].…”
Section: Chia and Quinoa Seed Extractsmentioning
confidence: 99%
“…Phenolic compounds are considered secondary plant metabolites that contain hydroxyl groups attached to at least one aromatic hydrocarbon ring. Although many phenolic compounds exist in a plant, such as phenolic acids, flavonoids, phenols, quinines, coumarins, lignans, phenylpropanoids, and xanthones [62], but flavonol glycosides mainly consist of quercetin and kaempferol, most abundantly present in quinoa. Polyphenol content in quinoa seeds varies between 0.46 and 1.84 mg/g of dry weight.…”
Section: Phenolicsmentioning
confidence: 99%
“…These are used to provide defense action in plants from insects. Also, these have other biological properties such as wound healing, antioxidant, antidiabetic, immunomodulatory, neuroprotective, and anti-depressive activities [62]. There are 13 phytoecdysteroids in quinoa seeds, of which 20-hydroxyecdysone (20HE) is abundantly present (around 62% to 90%).…”
Section: Phytoecdysteroidsmentioning
confidence: 99%